Improving the Performance of Sultan Agung Islamic Primary School Teachers through Training Models Based on Islamic Values and National Education Regulations - Nuridin Nuridin; Ira Alia Maerani (Universitas Islam Sultan Agung, 2021)
Teachers have a central position in the success of national educational goals. As mandated by Article 3 of Law No. 20 of 2003 on The National Education System. The purpose of national education is to develop the potential of learners to become human beings who believe and fear God Almighty, noble, healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. Therefore, the task of developing students according to the mandate of this regulation is the main target. For this reason, the Sultan Agung Waqf Board Foundation (YBWSA), one of which is engaged in primary a secondary education, feel it is important to develop the potential of teachers as quality human resources as mandated by national regulation. Human resources development is a key source of success in increasing teacher motivation and performance in the Sultan Agung Islamic Elementary School (SD) through a training model based on Islamic values. Improving the quality of performance is based on three keys to success, namely taqwa, knowledge and jamaah. Understanding the three keys to success is done through the training model of Islamic worldview, Islamic School Culture and Tahsin Prayer